Daughter Of Deliverance - Morris, Gilbert; Nang Chan Yeema (Bloomington, Minnesota, United States Bethany House Publishers, 2006)
Gilbert Morris tells the story of two star-crossed lovers on opposite sides of a war. One trying to save her family and the other trying to save his people''.
Keywords: Young Adult